Biochemical characterization of essential cell division proteins FtsX and FtsE that mediate peptidoglycan hydrolysis by PcsB in Streptococcus pneumoniae. Issue 5 (10th May 2016) - Bajaj, Ruchika; Bruce, Kevin E.; Davidson, Amy L.; Rued, Britta E.; Stauffacher, Cynthia V.; Winkler, Malcolm E.
Abstract: The FtsEX:PcsB complex forms a molecular machine that carries out peptidoglycan (PG) hydrolysis during normal cell division of the major respiratory pathogenic bacterium, Streptococcus pneumoniae (pneumococcus). FtsX is an integral membrane protein and FtsE is a cytoplasmic ATPase that together structurally resemble ABC transporters. Instead of transport, FtsEX transduces signals from the cell division apparatus to stimulate PG hydrolysis by PcsB, which interacts with extracellular domains of FtsX. Structural studies of PcsB and one extracellular domain of FtsX have recently appeared, but little is known about the biochemical properties of the FtsE ATPase or the intact FtsX transducer protein. We report here purifications and characterizations of tagged FtsX and FtsE proteins. Pneumococcal FtsX‐GFP‐His and FtsX‐His could be overexpressed in Escherichia coli without toxicity, and FtsE‐His remained soluble during purification. FtsX‐His dimerizes in detergent micelles and when reconstituted in phospholipid nanodiscs. FtsE‐His binds an ATP analog with an affinity comparable to that of ATPase subunits of ABC transporters, and FtsE‐His preparations have a low, detectable ATPase activity. However, attempts to detect complexes of purified FtsX‐His, FtsE‐His, and PcsB‐His or coexpressed tagged FtsX and FtsE were not successful with the constructs and conditions tested so far. In working with nanodiscs, we found that PcsB‐His has an affinity for charged phospholipids, mediated partly by interactions with its coiled‐coil domain. Together, these findings represent first steps toward reconstituting the FtsEX:PcsB complex biochemically and provide information that may be relevant to the assembly of the complex on the surface of pneumococcal cells. Abstract : The FtsEX:PcsB complex forms a molecular machine that carries out peptidoglycan (PG) hydrolysis during normal cell division of the major respiratory pathogenic bacterium, Streptococcus pneumoniae (pneumococcus). We report the purification and biochemical characterization of S. pneumoniae FtsE and full‐length FtsX, including initial attempts to isolate and reconstitute the FtsEX:PcsB complex biochemically in detergent micelles and nanodiscs and to determine the ATP binding and ATPase activity of pneumococcal FtsE.